2007
DOI: 10.1002/bit.21359
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐up from shake flasks to fermenters in batch and continuous mode with Corynebacterium glutamicum on lactic acid based on oxygen transfer and pH

Abstract: Scale-up from shake flasks to fermenters has been hampered by the lack of knowledge concerning the influence of operating conditions on mass transfer, hydromechanics, and power input. However, in recent years the properties of shake flasks have been described with empirical models. A practical scale-up strategy for everyday use is introduced for the scale-up of aerobic cultures from shake flasks to fermenters in batch and continuous mode. The strategy is based on empirical correlations of the volumetric mass t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 48 publications
4
45
0
Order By: Relevance
“…Furthermore, Seletzky et al (2007) demonstrated that, in a medium designed for C. glutamicum cultures, the value of the k L a in fresh culture medium could be assumed equal to the k L a value in water, as far as liquid viscosity remained unchanged [13].…”
Section: 2 E F F E C T O F G a S -L I Q U I D M A S S T R A N S Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Seletzky et al (2007) demonstrated that, in a medium designed for C. glutamicum cultures, the value of the k L a in fresh culture medium could be assumed equal to the k L a value in water, as far as liquid viscosity remained unchanged [13].…”
Section: 2 E F F E C T O F G a S -L I Q U I D M A S S T R A N S Fmentioning
confidence: 99%
“…This coefficient has been measured in shake flasks using conventional systems equipped with sensor spots for online dissolved oxygen monitoring or using the sulfites reaction method [21], [26][27][28]. Moreover, mathematical models and empirical correlations have also been used for gas-liquid mass transfer coefficient modeling [13,24], [29][30]. However, no literature data linking organic acids production by C. glutamicum and oxygen transfer in shake flasks could be found.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Commercial versions of RAMOS are available from Kuhner (Birsfelden, Switzerland) or Hitech Zang (Herzogenrath, Germany). This device has already been intensively in other investigations to study and characterize microbial systems (30)(31)(32). Offline sampling was conducted with the help of parallel 250-ml unbaffled shake flasks running simultaneously under identical conditions (30°C; 50-mm shake diameter) as the RAMOS cultivations in a ISF-4-W Kuhner shaker (Birsfelden, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…To this end, significant attention needs to be paid to provide scientists with detailed and precise models to gain sufficient understanding about behavior of the dynamic systems [11]. In addition, mathematical models are important for computational simulations, provided that the accuracy and limitations of the model are considered [12], [13].…”
Section: Introductionmentioning
confidence: 99%